Post-reactor blends of linear low density polyethylene

The linear low-density polyethylene copolymer prepared by using spray-dried ethanol-modified Ziegler-Natta catalyst and bridged bis(indenyl)zirconium dicetyl catalyst was solved, and the puncture characteristics and thermal viscosity-induced temperature of the film were optimized.

CN119816416APending Publication Date: 2025-04-11UNIVATION TECH LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380047928.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, when preparing linear low-density polyethylene copolymers, it is difficult to achieve a reduction in the average extruder die pressure during the film formation process, while maintaining the puncture characteristics of the film and reducing the thermal viscosity initiation temperature.

Method used

C4-LLDPE was prepared using spray-dried ethanol-modified Ziegler-Natta catalyst and C6-LLDPE was prepared using a bridged bis(indenyl)zirconium dicetyl catalyst, and the two were blended by a post-reactor method to form an LLDPE blend with a specific density and melt index.

Benefits of technology

It is achieved to reduce the average extruder die pressure during the film formation process, while maintaining the puncture characteristics of the film and reducing the thermal viscosity initiation temperature, achieving a balance between processability and mechanical characteristics required for the preparation of blown films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816416A_ABST
    Figure CN119816416A_ABST
Patent Text Reader

Abstract

A post-reactor blend of a linear low density polyethylene copolymer ("LLDPE blend"), the post-reactor blend of a linear low density polyethylene copolymer comprising: a linear low density ethylene / 1-butene copolymer, the linear low density ethylene / 1-butene copolymer is prepared by copolymerizing a polyethylene and 1-butene using a spray dried ethanol modified Ziegler-Natta catalyst; and a linear low density ethylene / 1-hexene copolymer prepared by copolymerizing a polyethylene and 1-hexene using a bridged bis (indenyl) zirconocene catalyst. And a film comprising the LLDPE blend. The invention also provides a method for preparing the LLDPE blend. A method of making the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Polyethylene, plastic films, polymerization processes and methods. Background Art

[0002] Patent application publications and patents in or relating to this field include US 5,756,193; US 9,273,170 B2; US 9,394,393 B2; US 9,447,265 B2; US 9,605,100 B2; US 9,714,305 B2; US11,248,066 B2; US 2017 / 0233507 A1; US ​​2018 / 0079836 A1; US ​​2022 / 0025135 A1; WO2009 / 040139 A1; WO 2019 / 112929 A1; WO 2020 / 102385 A1; WO 2020 / 223191 A1; and WO2021 / 026134 A1. Summary of the invention

[0003] Embodiments of the present invention include:

[0004] A post-reactor blend of linear low density polyethylene copolymers ("LLDPE blend"), the post-reactor blend of linear low density polyethylene copolymers comprising: a linear low density ethylene / 1-butene copolymer ("C4-LLDPE"), the linear low density ethylene / 1-butene copolymer being prepared by copolymerizing ethylene and 1-butene using a spray dried ethanol modified Ziegler-Natta catalyst ("sdEtOH / ZN"); and a linear low density ethylene / 1-hexene copolymer ("C6-LLDPE"), the linear low density ethylene / 1-hexene copolymer being prepared by copolymerizing ethylene and 1-hexene using a bridged bis(indenyl) zirconocene catalyst.

[0005] A post-reactor method for preparing the above-mentioned LLDPE blend comprises: melting the solid of the C4-LLDPE to form a melt thereof; melting the solid of the C6-LLDPE to form a melt thereof; and mixing the melts together to form the LLDPE blend.

[0006] A method for preparing a film comprising the above LLDPE blend.

[0007] A film comprising the above LLDPE blend. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 is a schematic cross-sectional view of a multilayer film structure including three film layers.

[0009] Figure 2 is a schematic cross-sectional view of a multilayer film structure including seven film layers. DETAILED DESCRIPTION

[0010] Activator (for Ziegler-Natta procatalyst): trialkylaluminum compound, dialkylaluminum chloride compound, dialkylaluminum alkoxide compound, alkylaluminum dichloride compound, or a combination of any two or more thereof. Examples are triethylaluminum (TEA), triisobutylaluminum (TIBA), tri(n-hexyl)aluminum (TnHAl), diethylaluminum chloride (DEAC), diethylaluminum ethoxide (DEAE), ethylaluminum dichloride (EADC), or a combination of any two or more thereof. For example, a combination of EADC and TEA. The molar ratio of the aluminum of the activator to the titanium of the Ziegler-Natta procatalyst (Al / Ti molar ratio) can be 1000:1 to 0.5:1, alternatively 300:1 to 1:1, alternatively 150:1 to 1:1.

[0011] Activator (for metallocene procatalyst): Lewis acid, non-coordinating ion activator, or ionizing activator, or Lewis base, alkylaluminum or alkylaluminoxane (alkylaluminoxane / alkylalumoxane). The activator can be methylaluminoxane (MAO), ethylaluminoxane, 2-methylpropyl-aluminoxane or modified methylaluminoxane (MMAO). The molar ratio of aluminum of the activator to zirconium of the bridged bis(indenyl) zirconocene procatalyst (Al / Zr molar ratio) can be 1000:1 to 0.5:1, alternatively 300:1 to 1:1, alternatively 150:1 to 1:1.

[0012] The term "bridged bis(indenyl) zirconocene" means a bidentate ligand-metal complex wherein the metal is Zr and the bidentate ligand comprises two indene derivatives bonded together by a divalent bridging group. The two indene derivatives may be independently selected from: unsubstituted indenyl anions, substituted indenyl anions, unsubstituted tetrahydroindenyl anions, and substituted tetrahydroindenyl anions. The substituents on the substituted indenyl or substituted tetrahydroindenyl may be alkyl, aryl, or aralkyl. "Tetrahydroindenyl" as used herein means 4,5,6,7-tetrahydroindenyl, and bridged tetrahydroindenyl means 4,5,6,7-tetrahydro-1-indenyl.

[0013] 1-Butene or "C4" or "C4": a compound of the formula H2C=CHCH2CH3.

[0014] Ethylene or "C2" or "C2": a compound of the formula H2C=CH2.

[0015] Film: A continuous layer of polymeric material having a thickness of greater than 0 micrometers (μm) to 250 μm as defined in ASTM terminology D883. Film thickness is measured according to ASTM D6988-21, Standard Guide for Determination of Thickness of Plastic Film Test Specimens.

[0016] 1-Hexene or "C6" or "C6": compound of the formula H2C=CHCH2CH2CH2CH3.

[0017] Ethanol or "EtOH": a compound of formula CH3CH2OH.

[0018] Intra-reactor: Occurs during the polymerization process and at locations inside the polymerization reactor.

[0019] In-reactor blend: A mixture prepared in a polymerization reactor by preparing a second polymer in situ in the presence of a first polymer in a polymerization reactor, and wherein the first polymer is prepared prior to preparing the second polymer or the first and second polymers are prepared together simultaneously.

[0020] LLDPE: Linear low-density polyethylene.

[0021] Modifier compounds: Acyclic or cyclic oxygen heterohydrocarbons composed of carbon, hydrogen and oxygen atoms.

[0022] Postreactor: occurs after the polymerization process is complete and at a location external to the polymerization reactor, ie, not involving in-reactor processes or blending.

[0023] Post-reactor blend: A mixture prepared outside a polymerization reactor by preparing a first polymer and a second polymer separately from each other and then mixing the first polymer and the second polymer together in a mixing device after the preparation steps are completed. The mixing device can be a mixer or a melt extruder. Due to the different conditions for preparing the second polymer, at least the chemical composition and properties of the second polymer of the post-reactor blend are different from the chemical composition and properties of the second polymer of the in-reactor blend. When the first polymer and the second polymer are prepared together simultaneously, due to the different conditions for preparing the first polymer, the chemical composition and properties of the first polymer of the post-reactor blend are also different from the chemical composition and properties of the first polymer of the in-reactor blend.

[0024] Procatalyst: A catalyst precursor that produces a catalyst when contacted with an activator.

[0025] Tetrahydrofuran or "THF": a monocyclic ether of formula C4H8O.

[0026] Ziegler-Natta catalyst: usually a titanium catalyst and optional silicon dioxide supported on a magnesium dichloride solid. The catalyst is prepared by contacting a Ziegler-Natta procatalyst with the above-mentioned activator. Typical Ziegler-Natta (pro) catalysts include titanium (IV) compounds (e.g., Ti (O-isopropyl) 4 or TiCl 4) supported on a magnesium halide (e.g., MgCl 2 ) solid and optional hydrophobic pyrogenic silica (e.g., Cab-O-Sil TS-610). Procatalysts may be unmodified (i.e., free of modifier compounds), or Ziegler-Natta (pro) catalysts may be modified by modifier compounds. Modifier compounds may be unsubstituted ethers, unsubstituted alcohols, or combinations thereof; for example, tetrahydrofuran, ethanol, or a combination of tetrahydrofuran ("THF") and ethanol ("EtOH").

[0027] Unless otherwise indicated, zirconium means zirconium (IV).

[0028] One embodiment includes a post-reactor blend of a linear low density polyethylene copolymer ("LLDPE blend") that can be used to make films, the LLDPE blend comprising: a linear low density ethylene / 1-butene copolymer ("C4-LLDPE") having the following properties derived from preparation with a spray dried ethanol modified Ziegler-Natta catalyst (sdEtOH / ZN): a density of 0.910 g / cm3 (g / cm 3 ) to 0.935g / cm 3 and a melt index I2 (190°C, 2.16 kg) of 0.8 g / 10 min to 2.8 g / 10 min; and a linear low density ethylene / 1-hexene copolymer ("C6-LLDPE") having the following properties derived from a bridged bis(indenyl) zirconocene catalyst: a density of 0.915 g / cm 3 Up to 0.925g / cm 3 And the melt index I2 (190° C., 2.16 kg) is 0.7 g / 10 min to 1.4 g / 10 min.

[0029] The above post-reactor blend may have any of limitations (i) to (iii): (i) wherein the C4-LLDPE has at least one, alternatively all but one, alternatively each of the following sdEtOH / ZN catalyst derived properties: polydispersity Mw / Mn greater than 4.3; the ratio of the Mw of the fraction eluting between 93.0°C and 120.0°C divided by the Mw of the whole polymer eluting from 25.0°C to 120.0°C is greater than 2.0, alternatively greater than 2.1; CUMCDI<-0.5, wherein CUMCDI is the cumulative molecular weight comonomer distribution index; the Mw from 25°C to 3 measured by iCCD is greater than 1.0; 7°C eluted polymer fraction of 9.0 wt% to 12.0 wt%; and the polymer fraction eluted from 75°C to 93°C measured by iCCD is less than 44.5 wt%, wherein iCCD is an improved method for comonomer content distribution analysis; (ii) wherein the C6-LLDPE has at least one of the following characteristics derived from a bridged bis(indenyl) zirconocene catalyst: a polydispersity Mw / Mn of 2.5 to 4.0; and a long chain branching (LCB) value of 0.001 long chain branches / 1000 carbon atoms (LCB / 1000C) to 0.094 LCB / 1000C; and (iii) both of (i) and (ii) are limited. Methods for determining CUM CDI values, iCCD values, and LCB values ​​are described below.

[0030] The above-mentioned post-reactor blend may include: wherein the post-reactor blend does not contain low-density polyethylene, a reference linear low-density polyethylene different from C4-LLDPE and C6-LLDPE, or a high-density polyethylene; or wherein the post-reactor blend contains low-density polyethylene, a reference linear low-density polyethylene different from C4-LLDPE and C6-LLDPE, or a high-density polyethylene.

[0031] Another embodiment includes a post-reactor method for preparing the above-mentioned LLDPE blend, which includes: melting a solid of C4-LLDPE to form a melt thereof; melting a solid of C6-LLDPE to form a melt thereof; and mixing the melts together to form an LLDPE blend. Embodiments of the method include: (i) mixing a solid of C4-LLDPE with a solid of C6-LLDPE to form a solid mixture thereof, and melting the solid mixture; (ii) mixing a solid of one of C4-LLDPE or C6-LLDPE into a melt of the other of C4-LLDPE or C6-LLDPE, and melting the solids; or (iii) preparing a melt of C4-LLDPE and a melt of C6-LLDPE separately, and mixing the melts together; or (iv) a combination of any two or more of embodiments (i) to (iii).

[0032] Prior to the melting step, the method may include preparing a C4-LLDPE having sdEtOH / ZN catalyst-derived properties by copolymerizing ethylene and 1-butene using a spray-dried ethanol-modified Ziegler-Natta catalyst ("sdEtOH / ZN"), wherein the spray-dried ethanol-modified Ziegler-Natta catalyst is prepared from the following materials: a titanium compound, which is Ti(O-isopropyl)4 or TiCl4 or TiCl3 / AlCl3; magnesium dichloride (MgCl2); hydrophobic fumed silica; a modifier compound, which comprises ethanol and optionally tetrahydrofuran; and an aluminum compound, which is selected from trialkylaluminum. , alkylaluminum dichloride, dialkylaluminum chloride or a combination of any two or more thereof; and preparing a C6-LLDPE having characteristics derived from a bridged bis(indenyl) zirconocene catalyst by copolymerizing ethylene and 1-hexene using a bridged bis(indenyl) zirconocene catalyst, wherein the bridged bis(indenyl) zirconocene catalyst is selected from the group consisting of: ethylenebis(2-methylindenyl) zirconium catalyst, dimethylsilylbis(2-methylindenyl) zirconium catalyst, diphenylsilylbis(2-methylindenyl) zirconium catalyst, diphenylsilylbis(2-methyl, 4-phenyl-indenyl) zirconium catalyst and diethylsilylbis(2-methyl, 4-phenyl-indenyl) zirconium catalyst. In some embodiments, the bridged bis(indenyl) zirconocene catalyst is selected from the group consisting of ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, In some embodiments, the bridged bis(indenyl) zirconocene catalyst is rac-dimethylsilyl-bis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride (CAS No.: 126642-97-5) or rac-dimethylsilyl-bis(4,5,6,7-tetrahydro-1-indenyl) zirconium dimethyl, wherein racemic means a racemate. The copolymerization steps are carried out separately in gas phase polymerization reactors.

[0033] In some embodiments, the bridged bis(indenyl) zirconocene catalyst is rac-dimethylsilyl-bis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride (CAS No. 126642-97-5), where rac means a racemate. The catalyst also has the name rac-dimethylsilylene-bis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride (IV) and the following structure: The catalyst can be used as XCAT TM EZ-100 catalyst is commercially available from Univation Technologies, LLC, Houston, Texas ("UNIVATION"), a wholly owned subsidiary of The Dow Chemical Company, Midland, Michigan.

[0034] Another embodiment includes a membrane comprising the above-described post-reactor blend.

[0035] The above-mentioned film may include: wherein the film is a monolayer film consisting of one layer, and wherein the one layer comprises a post-reactor blend; or wherein the film is a multilayer film consisting of 3 to 12 layers, wherein at least one of the 3 to 12 layers comprises a post-reactor blend.

[0036] The above-mentioned film may include: wherein the film is a multilayer film consisting of 3 to 12 layers, the multilayer film including 2 to 4 outer layers and 1 to 8 core layers; wherein at least one outer layer independently contains 70 wt% to 98 wt% C4-LLDPE and 30 wt% to 2 wt% C6-LLDPE, all based on the total weight of C4-LLDPE plus C6-LLDPE in at least one outer layer; and wherein at least one core layer independently contains 80 wt% to 100 wt% C4-LLDPE and 20 wt% to 0 wt% C6-LLDPE, all based on the total weight of C4-LLDPE plus C6-LLDPE in at least one core layer.

[0037] Another embodiment includes a method for preparing the above-mentioned multilayer film, which comprises: extruding at least one melt of the LLDPE blend through different dies among 3 to 12 dies, and optionally extruding a melt of C4-LLDPE through different dies among the dies, thereby preparing a multilayer film consisting of 3 to 12 layers.

[0038] The above embodiments can be further described by the following features and examples of the invention.

[0039] With respect to a first comparative LLDPE blend or a second comparative LLDPE blend of comparative C4-LLDPE and comparative C6-LLDPE (e.g., Comparative Examples CE1 or CE2 described later) (wherein the comparative C4-LLDPE component is prepared by comparative ethanol-free Ziegler-Natta catalyst UCAT TM J), the inventive LLDPE blend of the inventive C4-LLDPE and C6-LLDPE (e.g., inventive Example IE1 described later) (wherein the inventive C4-LLDPE component is prepared from a spray-dried ethanol-modified Ziegler-Natta catalyst) has a reduced average extruder die pressure during film formation. In addition, relative to the first comparative film or the second comparative film made from the first comparative LLDPE blend or the second comparative LLDPE blend, respectively (e.g., Comparative Film 1 or Comparative Film 2 described later), the inventive film 4 prepared from the inventive LLDPE blend maintains similar film puncture characteristics and has a reduced hot tack initiation temperature. Alternatively, relative to the third comparative LLDPE blend of comparative C4-LLDPE and comparative C6-LLDPE (e.g., Comparative Example CE3) (wherein the comparative C4-LLDPE component is prepared from a comparative ethanol-free Ziegler-Natta catalyst UCAT TM J), the inventive LLDPE blends of the inventive C4-LLDPE and the inventive C6-LLDPE (e.g., inventive Example IE1) have similar average extruder die pressures; and also the inventive film 4 prepared from the inventive LLDPE blend has improved film puncture characteristics and reduced hot tack initiation temperature relative to the third comparative film 3 prepared from the third comparative LLDPE blend.

[0040] The LLDPE blend is a post-reactor blend of a linear low density polyethylene copolymer comprising: a linear low density ethylene / 1-butene copolymer (C4-LLDPE) prepared by copolymerizing ethylene and 1-butene using a spray dried ethanol modified Ziegler-Natta catalyst ("sdEtOH / ZN"); and a linear low density ethylene / 1-hexene copolymer (C6-LLDPE) prepared by copolymerizing ethylene and 1-hexene using a bridged bis(indenyl) zirconocene catalyst. The copolymers are copolymerized in a gas phase polymerization reactor and at a UNIPOL TM The process is carried out under gas phase polymerization conditions. TMThe process has long been available from Univation Technologies, LLC of Houston, Texas, USA, and is described in numerous prior patents ("UNIVATION"). UNIVATION is a wholly owned subsidiary of The Dow Chemical Company ("DOW") of Midland, Michigan, USA.

[0041] The LLDPE blend has the balance between the processability characteristics required for preparing blown film and the mechanical characteristics and abuse characteristics required for the blown film to withstand the forces and loads that bulk packaging films withstand during transportation and storage. This characteristic balance is achieved by combining the sdEtOH / ZN catalyst characteristics including the density and melt index I2 of the C4-LLDPE described herein with the characteristics derived from the bridged bis(indenyl) zirconocene catalyst including the density and melt index I2 of the C6-LLDPE described herein. The characteristics derived from other catalysts described elsewhere herein can be used to further describe the characteristic balance of the LLDPE blend. Accordingly, the characteristics of the C4-LLDPE described herein are the results of the spray-dried ethanol-modified Ziegler-Natta catalyst used to prepare it, and the characteristics of the C6-LLDPE described herein are the results of the bridged bis(indenyl) zirconocene catalyst used to prepare it. This characteristic balance can be the characteristic balance described later for the embodiments of the present invention.

[0042] The selected properties of linear low density ethylene / 1-butene copolymer or "C4-LLDPE" are obtained and C4-LLDPE is prepared by copolymerizing ethylene and 1-butene using a spray-dried ethanol-modified Ziegler-Natta catalyst (sdEtOH / ZN). Although ethanol (EtOH) appears in its name, the sdEtOH / ZN catalyst also contains THF as a modifier compound. Therefore, the modifier compound of the sdEtOH / ZN catalyst of the present invention includes a combination of THF and EtOH. Therefore, another name for the catalyst is a spray-dried (tetrahydrofuran and ethanol) modified Ziegler-Natta catalyst ("sd(THF and EtOH) / ZN"). In some embodiments, the combination of THF and EtOH is composed of THF / EtOH in a weight / weight ratio of 2:1 to 1:2, alternatively 1.5:1.0 to 1.0:1.5, alternatively 1.1:1.0 to 1.0:1.1 (e.g., 1.0:1.0). In some such embodiments, the weight / weight ratio of THF / EtOH is 2:1 to 1:2, alternatively 1.5:1.0 to 1.0:1.5, alternatively 1.1:1.0 to 1.0:1.1, e.g., 1.0:1.0. Spray-dried ethanol-modified Ziegler-Natta catalyst is a titanium-based catalyst supported on magnesium dichloride and hydrophobic pyrogenic silica. Catalyst is prepared by contacting the titanium-based precatalyst of spray-dried ethanol-modified catalyst with an activator (such as triethylaluminum) in an inert hydrocarbon liquid (such as isopentane, hexane, toluene or mineral oil). The spray-dried ethanol-modified titanium-based procatalyst can be prepared from the following materials: a titanium compound, which is Ti(O-isopropyl)4 or TiCl4 or TiCl3 / AlCl3; magnesium dichloride (MgCl2); hydrophobic pyrogenic silica; a modifier compound, which comprises ethanol and optionally tetrahydrofuran; and an aluminum compound, which is selected from trialkylaluminum, alkylaluminum dichloride, and dialkylaluminum chloride. The trialkylaluminum can be triethylaluminum ("TEA" or "TEAl") or tri(n-hexyl)aluminum (TnHAl), the alkylaluminum dichloride can be ethylaluminum dichloride (EADC), and the dialkylaluminum chloride can be diethylaluminum chloride (DEAC). A combination of any two or more of them can be TEA and EADC or DEAC and TnHAl. The preparation can be carried out in an inert hydrocarbon liquid. Hydrophobic fumed silica can be prepared by treating untreated silica with a silicon-based hydrophobizing agent of the type described in US 11,248,066 B2, such as dimethyldichlorosilane. The hydrophobic fumed silica can be TS-610 from Cabot Corp. The catalyst can be a spray-dried ethanol-modified Ziegler-Natta catalyst as described in the Examples below.After copolymerization is complete and before post-reactor blending, a post-reactor treatment step deactivates the catalyst and removes ethanol, making the C4-LLDPE free of active catalyst and free of ethanol and any other volatile organic compounds. The C4-LLDPE may contain non-volatile residues of the catalyst, such as inactive Ti and Mg salts and silica.

[0043] The C4-LLDPE that contributes to the above-mentioned property balance of LLDPE blends has the following sdEtOH / ZN catalyst-derived properties: density of 0.910 g / cm3 (g / cm 3 ) to 0.935g / cm 3 , alternatively 0.915 g / cm 3 Up to 0.925g / cm 3 , alternatively 0.918 g / cm 3 Up to 0.922g / cm 3 ; and a melt index I2 (190°C, 2.16 kg) of 0.8 grams per 10 minutes (g / 10 min) to 2.8 g / 10 min, alternatively 1.5 g / 10 min to 2.5 g / 10 min, alternatively 1.7 g / 10 min to 2.2 g / 10 min.

[0044] In some embodiments, the C4-LLDPE also has at least one of the following sdEtOH / ZN catalyst-derived properties, alternatively all but one, alternatively each: a polydispersity Mw / Mn greater than 4.3; a ratio of the Mw of the fraction eluting between 93.0°C and 120.0°C divided by the Mw of the entire polymer eluted from 25.0°C to 120.0°C greater than 2.0, alternatively greater than 2.1; CUMCDI<-0.5, wherein CUMCDI is the cumulative molecular weight comonomer distribution index; the polymer fraction eluting from 25°C to 37°C measured by iCCD is 9.0 wt% to 12.0 wt%; and the polymer fraction eluted from 75°C to 93°C is less than 44.5 wt% measured by iCCD, wherein iCCD is an improved method for comonomer content distribution analysis.

[0045] Selected properties of linear low density ethylene / 1-hexene copolymers or "C6-LLDPE" are obtained and the C6-LLDPE is prepared by copolymerizing ethylene and 1-hexene using a bridged bis(indenyl) zirconocene catalyst. A bridged bis(indenyl) zirconocene catalyst is a metallocene catalyst in which the metal atom is zirconium and the two cyclopentadienyl ligands of the conventional metallocene are replaced by a single bidentate ligand containing a bridged bis(substituted indenyl) group. The bridged bis(indenyl) zirconocene catalyst may be selected from the group consisting of an ethylene bis(2-methylindenyl) zirconium catalyst, a dimethylsilyl bis(2-methylindenyl) zirconium catalyst, a diphenylsilyl bis(2-methylindenyl) zirconium catalyst, a diphenylsilyl bis(2-methyl, 4-phenylindenyl) zirconium catalyst, and a diethylsilyl bis(2-methyl, 4-phenylindenyl) zirconium catalyst. The bridged bis(indenyl) zirconocene catalyst is prepared by contacting a bridged bis(substituted indenyl) zirconium X2 procatalyst with an activator (e.g., MAO), wherein X is a halogen, an alkyl group, or a benzyl group; alternatively a chloride ion or a methyl group; alternatively a chloride ion. The bridged bis(substituted indenyl) zirconium X2 procatalyst may be selected from the group consisting of ethylene bis(2-methylindenyl) zirconium dichloride, dimethylsilyl bis(2-methylindenyl) zirconium dichloride, diphenylsilyl bis(2-methylindenyl) zirconium dichloride, diphenylsilyl bis(2-methyl, 4-phenylindenyl) zirconium dichloride, and diethylsilyl bis(2-methyl, 4-phenylindenyl) zirconium dichloride. These are reported in many patents, including in paragraph

[0095] of US2018 / 0079836 A1 and paragraph

[0111] of US2017 / 0233507 A1. Alternatively, the bridged bis(indenyl)zirconocene catalyst may be selected from the group consisting of ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl -1-indenyl) zirconium dimethyl, diphenylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride and diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dimethyl. These bridged bis(indenyl) zirconocene catalysts are prepared by contacting a bridged bis(4,5,6,7-tetrahydro-1-indenyl) zirconium X2 precatalyst with an activator (e.g., MAO), wherein X is a halogen, an alkyl group or a benzyl group; alternatively a chloride ion or a methyl group; alternatively a chloride ion.The bridged bis(indenyl) zirconocene X2 procatalyst may be selected from the group consisting of: ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, -1-indenyl) zirconium dimethyl, diphenylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dichloride and diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl) zirconium dimethyl. C6-LLDPE can be product EZP-2010, which is certified by UNIPOL. TM The PE process uses XCAT available from UNIVATION TM EZ-100 catalyst. C6-LLDPE can be product EZP-2010, which is produced by UNIPOL TM PE process using XCAT TM The C6-LLDPE is prepared with EZ-100 catalyst. After the copolymerization is completed and before the post-reactor blending, the post-reactor treatment step deactivates the catalyst so that the C6-LLDPE is free of active catalyst and any other volatile organic compounds. The C6-LLDPE may contain non-volatile residues of the bridged bis(indenyl) zirconocene catalyst, such as inactive Zr salts.

[0046] The C6-LLDPE that contributes to the above-mentioned balance of properties of the LLDPE blend has the following properties derived from the bridged bis(indenyl) zirconocene catalyst: density of 0.915 g / cm 3 Up to 0.925g / cm 3 , alternatively 0.920 g / cm 3 Up to 0.924g / cm 3 ; and a melt index I2 (190°C, 2.16 kg) of 0.7 g / 10 min to 1.4 g / 10 min, alternatively 0.9 g / 10 min to 1.2 g / 10 min. In some embodiments, C6-LLDPE has 0.922 g / cm 3 density and a melt index of 1.0 g / 10 min.

[0047] In some embodiments, the C6-LLDPE has at least one of the following properties (C) to (D) derived from a bridged bis (indenyl) zirconocene catalyst, alternatively all but one property, alternatively each property: (C) polydispersity Mw / Mn is 2.5 to 4.0; (D) long chain branching (LCB) value is 0.001 long chain branches / 1000 carbon atoms (LCB / 1000C) to 0.094 LCB / 1000C. In some embodiments, the C6-LLDPE is product EZP-2010.

[0048] It is believed that a reference LLDPE blend of a reference linear low density ethylene / 1-butene copolymer (reference C4-LLDPE) prepared using a different Ziegler-Natta catalyst (without ethanol) and a reference linear low density ethylene / 1-hexene copolymer (reference C6-LLDPE) prepared using a different metallocene catalyst (without a bridging indenyl ligand) will not achieve the balance of properties of the present invention.

[0049] A post-reactor method for preparing the above-mentioned LLDPE blend comprises: melting the solid of the C4-LLDPE to form a melt thereof; melting the solid of the C6-LLDPE to form a melt thereof; and mixing the melts together to form an LLDPE blend.

[0050] A method of preparing a film comprising the above-described LLDPE blend comprises extruding at least one melt of the LLDPE blend into a film having at least one layer. In a multilayer film laminate embodiment, the method comprises melting one or more embodiments of the LLDPE blend and optionally a single C4-LLDPE to obtain one or more melts thereof, and extruding the melts through a separate extruder configured to form a multilayer film laminate. The Alpine 7 film line can be used to carry out the process, wherein the multilayer film laminate consists of 7 layers, such as Figure 2 shown.

[0051] In one blown film embodiment, the method comprises: melting an LLDPE blend to obtain a melt thereof; extruding the melt through a die configured to form bubbles to produce bubbles of LLDPE copolymer; and blowing (inflating) the bubbles using a film blowing machine to produce a blown film. The LLDPE blend has a balance between the processability properties required to produce a blown film and the mechanical and abuse properties required for the blown film to withstand the forces and loads to which the bulk packaging film is subjected during transportation and storage.

[0052] Film preparation methods are well known. For example, see LyondellBasell, A Guide to Polyolefin Film Extrusion, Publication 6047 / 1004 (available from lyb.com) and Qenos Pty, Ltd., Film Extrusion and Conversion-Technical Guide (July 2015) (available from qenos.com).

[0053] A film comprising the above LLDPE blend. The film is particularly useful for packaging applications, such as food packaging, produced by standard film blowing methods and equipment.

[0054] Some embodiments of the film consist of a single layer ("monolayer film"), wherein the single layer consists of the LLDPE blend. This simple structure is not necessarily illustrated.

[0055] Other embodiments of the film consist of 2 or more layers ("multilayer films"), wherein at least one of the 2 or more layers consists of the inventive LLDPE blend, and each of the other of the 2 or more layers independently consists of a polyolefin composition selected from polypropylene, low density polyethylene (LDPE), single linear low density polyethylene (LLDPE), high density polyethylene (HDPE), the inventive LLDPE blend, or any combination of two or more such polyolefin compositions thereof. In some embodiments, at least two of the 2 or more layers independently consist of the inventive LLDPE blend.

[0056] Some embodiments of the multilayer film may consist of 3 to 12 layers, alternatively 5 to 12 layers, alternatively 6 to 12 layers, alternatively 7 layers, wherein at least one of the above layers consists of a LLDPE blend. In some such embodiments, the polyolefin compositions of any two or more consecutive layers are different. In other embodiments, the polyolefin compositions of two or more consecutive layers are the same, and this is referred to herein as "similar layer grouping".

[0057] In some embodiments, the film consists of 3 or more layers, wherein at least one of the 3 or more layers is a core layer (inner layer) composed of low density polyethylene (LDPE), and at least two of the 3 or more layers "sandwich" the core layer and independently consist of the same or different LLDPE blends.

[0058] An embodiment of a multilayer film comprising three layers consists of Figure 1exemplified by a 3-layer film 10 in . The 3-layer film 10 includes a first outer layer (skin layer or top layer) 20; a core layer (middle layer) 30; and a second outer layer (skin layer or bottom layer) 40. The core layer 30 is disposed between the top layer 20 and the bottom layer 40, i.e., the two layers 20 and 40 sandwich the core layer 30. The top layer 20, the core layer 30, and the bottom layer 40 are contacted and bonded together to form the 3-layer film 10. The term "core layer" refers to any internal layer in a multilayer film; and the phrase "skin layer" refers to the outermost layer of a multilayer film.

[0059] Will Figure 1 Each of the layers 20, 30 and 40 of the multilayer film 10 in is made into a different single layer. Figure 1 Such a 3-layer film 10 is made by a film forming process in which 3 different layers are arranged and combined in the following order: 20 / 30 / 40. All layers can be prepared simultaneously or sequentially or in any combination thereof. Reference numerals 21, 32 and 41 are in Figure 1 In the , it is simply used to indicate that layers 20, 30, and 40 are made into different monolayers (whether simultaneously or sequentially) in the film forming process. However, because layers 20, 30, and 40 (21, 31, and 41) are made from a melt of a polyethylene composition, these layers may undergo some interfacial mixing, so that in the final form, a cross-section of the 3-layer film 10 may appear to have fewer than three layers in total.

[0060] In other embodiments, Figure 1 The 3-layer film 10 in the embodiment of the present invention is part of a larger multilayer film having a total of 4 to 12 layers (including a total of 4 or more layers). Layers 20, 30, and 40 may include any three consecutive layers of a multilayer film having a total of 4 to 12 layers. In some such embodiments, layer 20 of the 3-layer film 10 is an outer or top layer, and layers 30 and 40 are core or inner layers of a multilayer film having a total of 4 to 12 layers. In other embodiments, each of layers 20, 30, and 40 is a core or inner layer of a multilayer film having a total of 4 to 12 layers.

[0061] In other embodiments, the multilayer film has a total of 4 to 12 layers. One embodiment is illustrated in Figure 2 7 layers of film 100.

[0062] exist Figure 2, similar layer grouping 200 consists of similar outer layers 21 and 22; similar layer grouping 300 consists of similar core layers 31, 32, and 33; and similar layer grouping 400 consists of similar outer layers 41 and 42. Layers 21 and 42 are outermost layers, respectively, and layers 22 and 41 are outer layers immediately adjacent to outermost layers 21 and 42, respectively. Outer layer 22 is disposed between outermost layer 21 and core layer 31. Outer layer 41 is disposed between outermost layer 42 and core layer 33. Core layer 32 is disposed between core layers 31 and 33. In some embodiments, core layers 31, 32, and 33 are independently composed of LLDPE that is not part of the present LLDPE blend, and outer layers 21, 22, 41, and 42 are independently composed of the same or different present LLDPE blends.

[0063] Figure 2 The 7-layer film 100 in is made by a film forming process in which 7 different layers are arranged and combined in the following order: 21 / 22 / 31 / 32 / 33 / 41 / 42. This can be done by a 7-layer film production line (such as an Alpine 7-layer film extruder).

[0064] In multilayer films (e.g. Figure 1 and Figure 2 In some embodiments of the multilayer films 10 and 100), at least one, alternatively each, outer layer (e.g., Figure 1 In the case of layers 20 and 40, alternatively in Figure 2 In the case of the outer layer, layers 21, 22, 41 and 42) independently contain 70 wt% to 98 wt% C4-LLDPE and 30 wt% to 2 wt% C6-LLDPE, alternatively 80 wt% to 97 wt% C4-LLDPE and 20 wt% to 3 wt% C6-LLDPE, alternatively 86 wt% to 94 wt% C4-LLDPE and 14 wt% to 6 wt% C6-LLDPE, alternatively 90 wt% C4-LLDPE and 10 wt% C6-LLDPE, all based on the total weight of C4-LLDPE plus C6-LLDPE in the outer layer.

[0065] In multilayer films (e.g. Figure 1 and Figure 2 In some embodiments of the multilayer films 10 and 100), at least one core layer, alternatively each core layer (e.g., Figure 1 In the case of the intermediate layer 30, alternatively in Figure 2% C4-LLDPE and 20 wt % to 0 wt % C6-LLDPE, alternatively 85 wt % to 100 wt % C4-LLDPE and 15 wt % to 0 wt % C6-LLDPE, alternatively 95 wt % to 100 wt % C4-LLDPE and 5 wt % to 0 wt % C6-LLDPE, alternatively 100 wt % C4-LLDPE and 0 wt % C6-LLDPE, all based on the total weight of C4-LLDPE plus C6-LLDPE in the core layer.

[0066] In some embodiments, at least one layer of the film also contains a polyolefin composition that is not part of the LLDPE blend of the present invention. Examples are reference LLDPE, low density polyethylene (LDPE), or high density polyethylene (HDPE). In some embodiments, Figure 1 The core layer 30 of the three-layer film 10 or Figure 2 The core layers 31, 32 and 33 of the 7-layer film 100 in the embodiment of the present invention are composed of a reference LLDPE which is not C4-LLDPE or C6-LLDPE, and Figure 1 Layers 20 and 40 and Figure 2 The layers 21, 22, 41 and 42 in the embodiment are independently composed of the same or different LLDPE blends of the present invention.

[0067] A method for preparing a film, the method comprising: extruding at least one melt of an LLDPE blend through at least two different dies, and optionally extruding a melt of a C4-LLDPE through at least one different die, thereby preparing a multilayer film having 3 to 12 layers. The polyethylene film can be prepared using any film extrusion line configured for preparing a multilayer film or any blown film line machine configured for preparing a polyethylene film.

[0068] The film extrusion line for preparing the multilayer film can be a film extrusion line configured for preparing a multilayer film having 3, 5, 7, 9 or up to 12 layers. An example of such a film extrusion line is an Alpine 7 film extruder configured for preparing a 7-layer multilayer film.

[0069] The film blowing machine can be configured with a feed hopper in fluid communication with an extruder, the extruder being in heated communication with a heating device capable of heating the polyethylene in the extruder to a temperature of up to 500° C. (e.g., 430° C.), and wherein the extruder is in fluid communication with a die head having an inner diameter of 20.3 cm (8 inches) and a fixed die gap (e.g., a gap of 1.778 mm (70 mils)), a blow-up ratio of 2.5:1, and a cooling line height (FLH) of 76 cm ± 10 cm (30 inches ± 4 inches) from the die head. Step (a) can be performed in the feed hopper. Steps (b) and (c) can be performed in the extruder and at a temperature of 400° C. to 450° C. (e.g., 430° C.). Step (d) can be performed in the die head and after leaving the die head. The machine may be capable of feed rates of (A) and (B) and a film production rate of 50 kilograms (kg) / hour to 200 kg / hour, for example, 91 kg (201 lbs) / hour at 430°C.

[0070] The film can be used to make containers and packages with enhanced optical properties. Examples of such containers are bags, such as ice packs and grocery bags. Examples of such packages are stretch film, meat wrap, and food wrap.

[0071] The film description focuses on packaging applications, but the applications of LLDPE blends are not limited to packaging films or even films in general. Useful applications for LLDPE blends also include various non-film articles (such as automotive parts).

[0072] Preparation method: Prepare specimens, test substrates or test sheets according to ASTM D4703-10, "Standard Practice for Compression Molding Thermoplastic Materials into Test Specimens, Plaques, or Sheets".

[0073] Density test method: Measured according to ASTM D792-13, "Standard Test Methods for Density and Specific Gravity (Relative Density) of Plastics by Displacement, Method B" (used to test solid plastics in liquids other than water, such as in liquid 2-propanol). In grams per cubic centimeter (g / cm 3 ) as the unit to report the results.

[0074] Melt Index ("I2") Test Method: For vinyl (co)polymers, it is measured according to ASTM D1238-13, using the condition of 190°C / 2.16kg (formerly known as "Condition E").

[0075] Molecular weights Mw (weight average), Mn (number average), and Mz (z average) are measured according to the High Temperature Gel Permeation Chromatography (GPC) test method described below.

[0076] High temperature gel permeation chromatography (GPC) test method: Performed on the sample to determine the molecular weight distribution (MWD) of the sample and the corresponding moments (Mn, Mw and Mz) of the sample. The chromatographic system used to measure GPC includes a Polymer Char GPC-IR high temperature GPC chromatograph (available from Polymer Char, Valencia, Spain), which is equipped with a 4-capillary differential viscometer detector and an IR5 multi-fixed wavelength infrared detector (available from Polymer Char). A Precision Detectors 2-angle laser scattering detector model 2040 (available from Precision Detector, currently available from Agilent Technologies) was added to the chromatographic system. A 15-degree angle of the light scattering detector was used for calculation purposes. Data collection was performed using GPC One software (available from Polymer Char). The system is equipped with an online solvent degasser (available from Agilent Technologies).

[0077] The detector chamber and column chamber of the chromatograph are both operated at 150°C. The columns used are 4 PLgel MixedA 7.5mm×300mm 20 micron columns (Agilent Technologies). The chromatographic solvent used is 1,2,4 trichlorobenzene (TCB) containing 200ppm butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume of each injection sample used to inject the sample is 200μL, and the flow rate is 1.0mL / min. In other words, the sample is prepared in a semi-automatic manner with PolymerChar "InstrumentControl" software, wherein the sample is targeted at a weight of 2mg / mL, and the solvent (containing 200ppm BHT) is added to the vial covered with a septum of pre-nitrogen bubbling via a PolymerChar high temperature autosampler. Under "low speed" shaking, the sample is dissolved at 160°C for 2 hours.

[0078] For routine molecular weight measurements, the GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards (available from Polymer Laboratories, now Varian) with molecular weights ranging from 580 to 8,400,000 and arranged in a 6-cocktail mixture. For molecular weights ≥ 1,000,000, the polystyrene standards were prepared at 0.025 g in 50 mL of solvent, and for molecular weights < 1,000,000, the polystyrene standards were prepared at 0.05 g in 50 mL of solvent. The polystyrene standards were dissolved at 80° C. with gentle stirring for 30 minutes. The narrow standards mixture was run first and in descending order starting with the highest molecular weight component to minimize degradation of the standards. The peak molecular weight of the polystyrene standards was converted to polyethylene molecular weight using the following equation (I): M 聚乙烯 =A*(M 聚苯乙烯 )^B Equation (I) , where in equation (I), "M" is the molecular weight of polystyrene or polyethylene; the value "A" is a positive number <0.500; and the value "B" is equal to 1.000. A fifth-order polynomial is used to fit the corresponding polystyrene calibration points. For the entire MWD range from the lowest MW to the highest MW, the MWD can also be expressed in the form of an integral of the cumulative weight distribution from zero to 1.00 relative to log(molecular weight) (Streigel et al., Modern Size Exclusion Liquid Chromatography 2nd Edition, P450).

[0079] The IR5 detector dosing was calibrated using at least ten ethylene-based polymer short chain branching (SCB) standards using octene as the comonomer. The polymer properties of the SCB standards are shown in the following SCB Standards Table. Each SCB standard has a narrow short chain branching distribution (SCBD) and a known comonomer content (e.g., 13C NMR method, Qiu et al., Anal. Chem. 2009, 81, 8585-8589) in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor over a single-site metallocene catalyst, the known monomer content ranges from homopolymer (0 SCB / 1000 total C) to about 40 SCB / 1000 total C, where total C=carbon in the main chain+carbon in the branch chain. Each SCB standard has a weight average molecular weight of 36,000 g / mole to 126,000 g / mole, as measured by GPC. An Mw of 36,000 g / mole indicates a polymer chain with about 1,290 equivalents of ethylene-derived constituent units, and an Mw of 126,000 g / mole indicates a polymer chain with about 4,510 equivalents of ethylene-derived constituent units. Additionally, each SCB standard has a molecular weight distribution (Mw / Mn) between 2.0 and 2.5, as described in the SCB Standards Table.

[0080] SCB Standard Product Table :

[0081] Octene comonomer (wt%) SCB / 1000 total C M Mw / Mn 23.1 28.9 37,300 2.22 14.0 17.5 36,000 2.19 0.0 0.0 38,400 2.20 35.9 44.9 42,200 2.18 5.4 6.8 37,400 2.16 8.6 10.8 36,800 2.20 39.2 49.0 125,600 2.22 1.1 1.4 107,000 2.09 14.3 17.9 103,600 2.20 9.4 11.8 103,200 2.26

[0082] The "IR5 Area Ratio" (or "IR5 Area Ratio") was calculated as the "baseline-subtracted area response of the IR5 methyl channel sensor" to the "baseline-subtracted area response of the IR5 measurement channel sensor" for each SCB standard (standard filters and filter wheels provided by PolymerChar). 甲基通道面积 / IR5 测量通道面积 ”). The linear fit of SCB frequency and IR5 area ratio was constructed in the form of the following equation (II): SCB / 1000 total C = A0 + [A1 × (IR5 甲基通道面积 / IR5 测量通道面积 )] Equation (II), where A0 is the SCB / 1000 total C intercept at zero IR5 area ratio, and A1 is the slope of SCB / 1000 total C vs. IR5 area ratio. A1 represents the increase in SCB / 1000 total C as a function of IR5 area ratio. For narrow PDI and narrow SCBD standard materials, the IR5 area ratio is equal to the IR5 height ratio.

[0083] A series of "linear baseline-subtracted chromatogram heights" of the chromatogram generated by the "IR5 methyl channel sensor" was established as a function of the column elution volume to generate a baseline-corrected chromatogram (methyl channel). A series of baseline-subtracted chromatogram heights of the chromatogram generated by the "IR5 measurement channel" of the IR-5 detector was established as a function of the column elution volume to generate a "baseline-corrected chromatogram (measurement channel)".

[0084] The "IR5 Height Ratio" of the "Baseline Corrected Chromatogram (Methyl Channel)" to the "Baseline Corrected Chromatogram (Measurement Channel)" is calculated at each column elution volume index (each equally spaced index represents 1 data point per second at a 1 mL / min elution flow rate) within the sample integration range. The IR5 Height Ratio is multiplied by the coefficient A1, and the coefficient A0 is added to this result to produce the predicted SCB frequency for the sample. The results are converted to the mole percent of comonomer using the following equation (III): Mole percent of comonomer = {SCB f / [SCB f +((1000-SCB f * length of the comonomer) / 2)]}*100Equation (III), where "SCB f ” is the “SCB per 1000 total C”, and the “comonomer length” is 8, which is the carbon number of octene.

[0085] Comonomer composition is reported relative to MWD as octene comonomer. Each elution volume index is converted to a molecular weight value (Mw) using the method described above. i ) value; Equation (II) calculates "comonomer mole percent (y-axis)" as Log(Mw i ) and calculate the slope between the cumulative weight fractions from 0.10 to 0.95. (Use EXCEL linear regression to calculate the slope and R between the cumulative weight fractions from 0.10 to 0.95 2 (Linear fit coefficient)). The slope is defined as the cumulative molecular weight comonomer distribution index (CUMCDI).

[0086] iCCD test method: "iCCD" is an improved method for comonomer content distribution (CCD) analysis; and is based on the method described in WO2017040127A1. The test method is carried out with a crystallization elution fractionation (CEF) instrument (available from PolymerChar) equipped with an IR-5 detector and a dual angle precision detector light scattering detector model 2040 (available from Agilent Technologies). Ortho-dichlorobenzene (ODCB, 99% anhydrous or industrial grade) is used as a solvent. Silica gel 40 (wherein the particle size is 0.2 mm to about 0.5 mm; available from EMD Chemicals) can be used to dry the ODCB solvent. The dried silica is filled into three empty HT-GPC columns (wherein the dimensions are 300 mm×7.5 mm (ID)) to further purify the ODCB solvent as an eluent. The CEF instrument is equipped with an automatic sampler with a nitrogen (N2) purge function. ODCB was bubbled with dry N2 for 1 hour before use.

[0087] Samples were prepared using an autosampler at 4 mg / mL (unless otherwise specified) with shaking at 160°C for 1 hour. The injection volume of the sample was 300 microliters (μL). The temperature profile of the iCCD was as follows: crystallization from 105°C to 30°C at 3°C / min; thermal equilibrium at 30°C for 2 minutes (including soluble fraction elution time set at 2 minutes); elution from 30°C to 140°C at 3°C / min. The flow rate of the sample during crystallization was 0.0 mL / min. The flow rate of the sample during elution was 0.50 mL / min. Data were collected at a rate of one data point per second.

[0088] The iCCD column used was a 15 cm (length) x 1.5 cm (2.5 cm) column filled with gold-coated nickel particles (Bright 7GNM8-NiS; available from Nippon Chemical Industrial Co.). 1 / 4 inner diameter (ID) stainless steel tube. The column was filled and conditioned using a slurry method according to the method described in WO2017040127A1. The final pressure of the trichlorobenzene (TCB) slurry filling was 150 bar (10 MPa).

[0089] The column temperature was calibrated using a mixture of the following: (i) 1.0 mg / mL linear homopolymer polyethylene (zero comonomer content, melt index (I2) of 1.0 g / cm 3 and the polydispersity (M) as determined by the GPC test method described above. w / M n ) polyethylene with a molecular weight of approximately 2.6) as a "reference material"; and (ii) ODCB containing 0.5 mg / mL eicosane. The iCCD temperature calibration consists of the following four steps: (1) calculating a delay volume defined as the measured peak elution temperature of eicosane minus a temperature offset of 30.00°C; (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data (it should be noted that this temperature offset is a function of experimental conditions such as elution temperature, elution flow rate, etc.); (3) creating a linear calibration line that converts the elution temperature within the range of 30.00°C to 140.00°C, such that the linear homopolymer polyethylene reference material has a peak temperature of 101.0°C and eicosane has a peak temperature of 30.0°C; (4) for the soluble fraction measured isothermally at 30°C, linearly extrapolating the elution temperature below 30.0°C by using an elution heating rate of 3°C / min according to the method described in U.S. Patent No. 9,688,795. GPCOne software (available from PolymerChar) was used to generate the SCBD distribution curve dWi / dT, where W i It is T i The mass under which T iis the calibrated elution temperature.

[0090] The elution fraction in weight % is determined under a specific elution temperature range. It is defined as the area of ​​the iCCD spectrum deducted by the baseline within a specific temperature range divided by the total integrated area of ​​the iCCD elution chromatogram deducted by the baseline multiplied by 100%. For example, weight % is (in the elution temperature range of 75.0°C to 93.0°C) defined as the area of ​​the iCCD chromatogram deducted by the baseline eluted from 75.0°C to 93.0°C divided by the total integrated area of ​​the iCCD chromatogram (from 25.0°C to 120.0°C) multiplied by 100%.

[0091] The elution temperature of comonomer content relative to iCCD was constructed using a solution method using 12 reference materials (ethylene homopolymers and ethylene-octene random copolymers with ethylene equivalent weight average molecular weights in the range of 35,000 to 128,000 prepared using a single-site metallocene catalyst). The analysis of all these reference materials was the same as the previously specified 4 mg / mL. The correlation between the comonomer mole fraction and the elution temperature (T in degrees Celsius) follows the following expression: ln (1-comonomer mole fraction) = -208.328 / (elution temperature + 273.12) + 0.55846.

[0092] The composition distribution index (CDBI) is defined as the weight percentage of polymer molecules having a comonomer content within + / - 50% of the median total molar comonomer content (as reported in WO 93 / 03093). The CDBI of a polyolefin can be conveniently calculated from SCBD data obtained from techniques known in the art, such as, for example, temperature rising elution fractionation ("TREF"), such as that described in Wild et al., Journal of Polymer Science, Poly. Phys. Ed., Vol. 20, 441 (1982); L.D. Cady, "The Role of Comonomer Type and Distribution in LLDPE Product Performance," SPE Regional Technical Conference, Quaker Square Hilton, Akron, OH, 107-119 (October 1-2, 1985); and U.S. Pat. Nos. 4,798,081 and 5,008,204.

[0093] Herein, the CDBI is accordingly calculated by using the short chain branching distribution measured by the iCCD method and the comonomer composition correlation as described above relative to the elution temperature.

[0094] The molecular weight of the polymer and the molecular weight of the polymer fractions were determined directly from the light scattering (LS) detector (precision detector, 90 degree angle) and the concentration detector (IR-5) by assuming the shape factor to be 1 and all virial coefficients equal to zero, giving the Rayleigh-Gans-Debys approximation (Striegel and Yau, Modern Size Exclusion Liquid Chromatogram, pp. 242 and 263). The baselines of both the LS and concentration detectors were subtracted. The integration window was set to integrate the entire chromatogram over the elution temperature range (temperature calibration specified above) from 23.0°C to 120°C.

[0095] Calculation of molecular weight (Mw) from iCCD includes the following steps: Step (1): Measure the inter-detector offset. The offset is defined as the geometric volume offset between the LS detector relative to the concentration detector. It is calculated as the difference in elution volume (mL) of the polymer peak between the concentration detector and the LS chromatogram. This is converted to a temperature offset by using the elution heat rate and the elution flow rate. The polydispersity Mw of linear high density polyethylene (comonomer content zero, melt index (I2) of 1.0, and conventional gel permeation chromatography) is used. w / M nis approximately 2.6). The same experimental conditions as the normal iCCD method described above were used, except for the following parameters: crystallization from 140°C to 137°C at 10°C / min, thermal equilibrium at 137°C for 1 minute as the soluble fraction elution time, soluble fraction (SF) time of 7 minutes, and elution from 137°C to 142°C at 3°C / min. The flow rate during crystallization was 0.0 ml / min. The flow rate during elution was 0.80 ml / min. The sample concentration was 1.0 mg / ml. Step (2): Before integration, each data point in the LS chromatogram was shifted to correct for inter-detector offset. Step (3): The baseline-subtracted LS and concentration chromatograms over the entire elution temperature range of step (1) were integrated. The MW detector constant was calculated by using known MW HDPE samples in the range of 100,000Mw to 140,000Mw and the area ratio of the LS and concentration integrated signals. Step (4): The Mw of the polymer is calculated by using the ratio of the integrated light scattering detector (90 degree angle) to the concentration detector and using the MW detector constant. Using the measured MW detector constant, NIST NBS1475a analyzed by the same method as specified in (1) above gives a molecular weight of 58,000. The Mw ratio is calculated as the Mw of the fraction eluted from 93.0°C to 120.0°C divided by the Mw of the whole polymer (eluted from 25.0°C to 120.0°C).

[0096] Long Chain Branching (LCB) Value Test Method: The amount of long chain branching (LCB) present in any LLDPE can be measured using nuclear magnetic resonance (NMR) spectroscopy as described in publications (A) to (C): Z. Zhou, S. Pesek, J. Klosin, M. Rosen, S. Mukhopadhyay, R. Cong, D. Baugh, B. Winniford, H. Brown, K. Xu, "Long chain branching detection and quantification in LDPE with special solvents, polarization transfer techniques, and inverse gated 13C NMR spectroscopy." (B) Z. Zhou, C. Anklin, R. Cong, X. Qiu, R. Kuemmerle, “Long-chain branch detection and quantification in ethylene-hexene LLDPE with 13C NMR,” Macromolecule, 2021, 54, 757; and (C) Z. Zhou, C. Anklin, R. Kuemmerle, R. Cong, X. Qiu, J. DeCesare, M. Kapur, R. Patel, “Very sensitive 13C NMR method for the detection and quantification of long-chain branches in ethylene-hexene LLDPE,” Macromolecule, 2018, 51, 8443, which includes teachings of pulse sequences; (B) Z. Zhou, C. Anklin, R. Cong, X. Qiu, R. Kuemmerle, “Long-chain branch detection and quantification in ethylene-hexene LLDPE with 13C NMR,” Macromolecule, 2021, 54, 757. ethylene-hexeneLLDPE)”, Macromolecule, 2021, 54, 5985.

[0097] Film Test Method for Transparency: Optical property transparency was measured according to ASTM D1746-15, Standard Test Method for Transparency of Plastic Sheeting. Transparency was measured using a BYK-Gardner Haze-Gard Plus. Transparency was expressed as a percentage of the intensity of light with and without the sample in the light path.

[0098] Film test method for falling dart impact resistance: measured according to ASTM D1709-16 "Standard Test Methods for Impact Resistance of Plastic Film by the Free-Falling Dart Method".

[0099] Film test method for Elmendorf multi-tear resistance: measured in the cross direction (CD) and machine direction (MD) according to ASTM D1922-15 (2020) "Standard Test Method for Propagation Tear Resistance of Plastic Film and Thin Sheeting by Pendulum Method".

[0100] Film test method for puncture resistance: measured according to ASTM D5748-95 (2012) "Standard Test Method for Protrusion Puncture Resistance of Stretch Wrap Film". The puncture resistance of the film is measured as the penetration resistance of the film by a probe hitting the film at a standard speed (such as 250 millimeters per minute (mm / min)). The probe is coated with polytetrafluoroethylene and has an outer diameter of 1.905 cm (0.75 inches). The film is clamped during the test. The probe eventually penetrates or destroys the clamped film. The mechanical testing software is used to record the peak force of the fracture, that is, the maximum force to destroy or penetrate the clamped film, the energy (work), and the damage distance when the probe penetrates. The probe applies a biaxial stress to the clamped film, which represents the type of stress encountered by the film in many end-use applications. This resistance is a measure of the energy absorption capacity of the film to resist puncture under these conditions.

[0101] Film Test Method for Gloss: Optical gloss is measured according to ASTM D2457-13, Standard Test Method for Specular Gloss of Plastic Films and Solid Plastics. Specular gloss is measured using a glass gage at an incident angle of 45°. Specular gloss has no units.

[0102] Film Test Method for Haze: Optical haze is measured according to ASTM D1003-13, Standard Test Method for Haze and Luminous Transmittance of Transparent Plastic. Haze is measured using a haze meter. Haze is expressed as the percentage of light transmission that deviates from the incident beam due to forward scattering when passing through the film.

[0103] Film Test Method for Hot Tack: Measured according to ASTM F-1921 (Method B) using an Enepay commercial testing machine. Prior to testing, the samples were conditioned at 23°C and 50% relative humidity (RH) for a minimum of 40 hours. The hot tack test simulates filling the material into a pouch or bag before the seal has a chance to cool completely. Sheets measuring 8.5 inches x 14 inches were cut from the film, with the longest dimension being the longitudinal direction. Strips 1" wide and 14" long were cut from the film [the sample only needs to be long enough for clamping]. These samples were tested over a range of temperatures and the results were reported as the maximum load as a function of temperature. The typical temperature step size was 10°C, with 6 repetitions at each temperature. The following are typical parameters used in the test: Sample width: 25.4 millimeters (mm, 1.0 inch); Sealing pressure: 0.275 Newtons / square millimeter (N / mm 2 ); Seal dwell time: 1.0 second (sec); Peel speed: 200 millimeters / second (mm / sec); Seal depth = 12.7 mm (0.5 inches). Data are reported as hot tack curves, where the average hot tack force in Newtons (N) is plotted as a function of temperature.

[0104] Film Test Method for 1% Secant Modulus: Measured in the CD and MD according to ASTM D882-12, Standard Test Methods for Tensile Properties of Thin Plastic Sheeting. Use 1% Secant Modulus in the CD or MD. Report results in megapascals (MPa). 1,000.0 pounds per square inch (psi) = 6.8948 MPa.

[0105] Film Test Method for Zebedee Transparency: Optical Zebedee transparency was measured according to ASTM D1746-15, Standard Test Method for Transparency of Plastic Sheeting. Transparency was measured using a Zebedee CL-100 meter. Zebedee transparency was expressed as a percentage of the intensity of light with and without the sample in the light path.

[0106] Example

[0107] Synthesis of an example of an EtOH-modified spray-dried Ziegler-Natta catalyst system of the present invention comprising a modifier compound, which is a 1:1 (wt / wt) combination of tetrahydrofuran and ethanol: See WO 2019 / 112929A1. Anhydrous ethanol (14 kilograms (kg)) and anhydrous tetrahydrofuran (14 kg) are added to a feed tank. Next, finely powdered solid MgCl2 (1255 g) is added. The mixture is heated to 60°C and mixed for 5 hours to overnight to form a third solution. The third solution is cooled to 40°C to 45°C. TiCl3.AA (459 g) is then added and mixed for 1 hour. "TiCl3.AA" is available from WR Grace and means a mixture of TiCl3 / AlCl3 in a molar ratio of 3:1, which can be obtained from a commercial supplier or can be prepared by 3 molar equivalents of TiCl4 and one molar equivalent of aluminum (Al) metal (Al) acting as a reducing agent. 0) in a solvent such as anhydrous tetrahydrofuran. Hydrophobic pretreated fumed silica (Cabosil TS-610, 1.6 kg) is then added to obtain a suspension. The suspension is mixed for 30 minutes to obtain a slurry of the modified Ziegler-Natta procatalyst system and the hydrophobic pretreated fumed silica. The slurry is blue. The slurry is sprayed in a spray dryer using the following conditions: inlet temperature 160°C, outlet temperature 110°C, feed rate of about 45 kg / hour, total gas flow of about 270 kg / hour, atomizer speed: typically varied by about 85% to obtain a spray-dried Ziegler-Natta procatalyst system modified by tetrahydrofuran / ethanol 1:1 (wt / wt). The EtOH modified spray dried Ziegler-Natta precatalyst system was contacted with a chemical reduction effective amount of 40 wt% trihexyl aluminum (TnHAl) reducing agent in a reagent mixture in mineral oil in a 4 liter (L) volume mixing tank for about 1 hour to obtain a reaction mixture, and then a 12 wt% diethyl aluminum chloride (DEAC) reagent mixture in mineral oil was added to the reaction mixture and mixed for another 1 hour to obtain a chemically reduced modified spray dried Ziegler-Natta catalyst. The molar ratio of TnHAl to DEAC was about 0.875 / 1.000.

[0108] Table 1: Polymerization conditions for preparing reference C4-LLDPE A and inventive C4-LLDPE B .

[0109]

[0110] Reference LLDPE A is a linear low density ethylene / 1-butene copolymer prepared by using the gas phase polymerization conditions listed in Table 1 above and a comparative ethanol-free tetrahydrofuran modified Ziegler-Natta catalyst (available from UNIVATION and The Dow Chemical Company as UCAT TM J sells) to prepare by copolymerizing ethylene and 1-butene. TM The J catalyst was not prepared using ethanol and does not contain ethanol.

[0111] The inventive C4-LLDPE B is a linear low density ethylene / 1-butene copolymer prepared by copolymerizing ethylene and 1-butene using a spray dried EtOH modified Ziegler-Natta catalyst version 1a, 1b, 2 or 3 and using the gas phase polymerization conditions listed in Table 1 above.

[0112] Reference LDPE C is a low density polyethylene (not LLDPE) sold by DOW under the product code LDPE 450E, which is produced in a high pressure polymerization process without catalyst.

[0113] The C6-LLDPE D of the present invention is a linear low-density ethylene / 1-hexene copolymer. The linear low-density ethylene / 1-hexene copolymer is prepared by using XCAT TM EZ-100 (a commercially available bridged bis(indenyl) zirconocene catalyst) and is prepared by copolymerizing ethylene and 1-hexene under gas phase conditions. LLDPE D is the product EZP-2010.

[0114] Table 2: C4-LLDPE A. C4-LLDPE B. LDPE C and C6-LLDPE Characteristics of D :

[0115]

[0116] *R 2 are linear fit coefficients and were calculated using EXCEL linear regression between cumulative weight fractions of 0.10 and 0.95; nr means “not reported”.

[0117] Table 3: Polyolefin compositions used to prepare the 7-layer films 1 to 4 shown in the following table .

[0118]

[0119] Table 4: Film extruder line parameters used to prepare the 7-layer films 1 to 4 shown in the following tables .

[0120] Die size: 9.84 inches (25 cm) Die gap: 78.7 mils (2mm) Blowing ratio (BUR): 2.5 Height of frost line 35 inches (89 cm) Output rate: 310 lbs / hr (141 kg / hr)

[0121] Table 5: The head pressure of the Alpine 7 film extruder line used to make 7-layer films 1 to 4 is shown in the table below :

[0122] Example No.: Comparative Example A Comparative Example B Comparative Example C Embodiment 1 of the present invention 7-layer film number: 1 2 3 4 Die head pressure extruder 1, MPa 28.0 27.0 24.5 26.0 Die head pressure extruder 2, MPa 29.5 29.5 27.4 28.1 Die head pressure extruder 3, MPa 25.0 25.5 23.3 23.2 Die head pressure extruder 4, MPa 23.4 23.9 22.1 22.2 Die head pressure extruder 5, MPa 22.4 22.6 21.4 21.5 Extruder head pressure 6, MPa 30.2 29.9 27.8 28.0 Extruder head pressure 7, MPa 28.8 28.1 26.4 25.8 Average pressure 1-7, MPa 26.8 26.6 24.7 25.0

[0123] Table 6: Comparison of 7-layer films 1 :

[0124]

[0125] Table 7: Comparison of 7-layer films 2 :

[0126]

[0127] Table 8: Comparison of 7-layer films 3 :

[0128]

[0129] Table 9: 7-layer film 4 of the present invention :

[0130]

[0131] Table 10: Properties of 7-layer films 1 to 4 with a thickness of 51 μm (2 mils):

[0132]

[0133] Table 11: Hot Tack of 7-Layer Films 1 to 4 with a Thickness of 51 μm (2 mils) :

[0134] Example number: Comparative Example A Comparative Example B Comparative Example C Embodiment 1 of the present invention type Compare Compare Compare The present invention 7-layer film number 1 2 3 4 Temperature(℃) Hot viscosity, Newton (N) Hot viscosity (N) Hot viscosity (N) Hot viscosity (N) 80 0.3 0.3 0.3 0.5 90 0.3 0.3 0.3 0.6 100 1.0 0.8 1.1 1.6 110 2.0 2.2 2.1 2.1 120 1.8 2.1 1.8 1.9

[0135] The inventive LLDPE blend of IE1 has a reduced average extruder die pressure during film formation relative to the comparative LLDPE blends of Comparative Example A and Comparative Example B. In addition, relative to Comparative Film 1 and / or Comparative Film 2, Inventive Film 4 still maintains similar film puncture properties and has a reduced hot tack initiation temperature.

[0136] Inventive LLDPE blend IE1 has similar average extruder die pressure relative to comparative LLDPE blend Comparative Example C, and also Inventive Film 4 has improved film puncture characteristics and reduced hot tack initiation temperature relative to Comparative Film 3.

Claims

1. A post-reactor blend of linear low density polyethylene copolymers ("LLDPE blend") useful for preparing films, the LLDPE blend comprising: a linear low density ethylene / 1-butene copolymer ("C4-LLDPE") having the following properties derived from preparation with a spray dried ethanol modified Ziegler-Natta catalyst (sdEtOH / ZN): a density of 0.910 g / cm3 (g / cm 3 ) to 0.935g / cm 3 and a melt index I2 (190°C, 2.16 kg) of 0.8 g / 10 min to 2.8 g / 10 min; and a linear low density ethylene / 1-hexene copolymer ("C6-LLDPE") having the following properties derived from a bridged bis(indenyl) zirconocene catalyst: a density of 0.915 g / cm 3 Up to 0.925g / cm 3 And the melt index I2 (190° C., 2.16 kg) is 0.7 g / 10 min to 1.4 g / 10 min.

2. The post-reactor blend of claim 1, having any one of limitations (i) to (iii): (i) wherein the C4-LLDPE has at least one, alternatively all but one, alternatively each of the following sdEtOH / ZN catalyst derived properties: polydispersity Mw / Mn greater than 4.3; the ratio of the Mw of the fraction eluting between 93.0°C and 120.0°C divided by the Mw of the whole polymer eluted from 25.0°C to 120.0°C is greater than 2.0, alternatively greater than 2.1; CUMCDI<-0.5, wherein CUMCDI is the cumulative molecular weight comonomer distribution index; the polymer fraction eluting from 25°C to 37°C is 9.0 wt% to 12.0 wt% as measured by iCCD; and the polymer fraction eluting from 75°C to 93°C is less than 44.5 wt% as measured by iCCD, wherein iCCD is an improved method for comonomer content distribution analysis; (ii) wherein the C6-LLDPE has at least one of the following bridged bis(indenyl) zirconocene catalyst-derived properties: a polydispersity Mw / Mn of 2.5 to 4.0; and a long chain branching (LCB) value of 0.001 long chain branches / 1000 carbon atoms (LCB / 1000C) to 0.094 LCB / 1000C; and (iii) Limit both (i) and (ii).

3. The post-reactor blend of claim 1 or claim 2, wherein the post-reactor blend is free of low density polyethylene, a reference linear low density polyethylene different from the C4-LLDPE and the C6-LLDPE, or a high density polyethylene; or wherein the post-reactor blend comprises low density polyethylene, a reference linear low density polyethylene different from the C4-LLDPE and the C6-LLDPE, or a high density polyethylene.

4. The post-reactor blend of any one of claims 1 to 3, wherein the bridged bis(indenyl)zirconocene catalyst is rac-dimethylsilylene-bis(4,5,6,7-tetrahydro-1-indenyl)zirconium(IV) dichloride.

5. A post-reactor process for preparing a LLDPE blend according to any one of claims 1 to 4, the process comprising: Melting the solid of the C4-LLDPE to form a melt thereof; Melting the solid of the C6-LLDPE to form a melt thereof; and mixing the melts together to form the LLDPE blend.

6. The method according to claim 5, before the melting step, comprising: The C4-LLDPE having the properties derived from a spray-dried ethanol-modified Ziegler-Natta catalyst ("sdEtOH / ZN") is prepared by copolymerizing ethylene and 1-butene using a spray-dried ethanol-modified Ziegler-Natta catalyst ("sdEtOH / ZN"), wherein the spray-dried ethanol-modified Ziegler-Natta catalyst is prepared from the following materials: a titanium compound, wherein the titanium compound is Ti(O-isopropyl)4 or TiCl4 or TiCl3 / AlCl3; magnesium dichloride (MgCl2); hydrophobic fumed silica; a modifier compound, wherein the modifier compound comprises ethanol and optionally tetrahydrofuran; and an aluminum compound, wherein the aluminum compound is selected from trialkylaluminum, alkylaluminum dichloride, dialkylaluminum chloride, or a combination of any two or more thereof; and The C6-LLDPE having the characteristics derived from the bridged bis(indenyl) zirconocene catalyst is prepared by copolymerizing ethylene and 1-hexene using the bridged bis(indenyl) zirconocene catalyst, wherein the bridged bis(indenyl) zirconocene catalyst is selected from the group consisting of: ethylenebis(2-methylindenyl) zirconium catalyst, dimethylsilylbis(2-methylindenyl) zirconium catalyst, diphenylsilylbis(2-methylindenyl) zirconium catalyst, diphenylsilylbis(2-methyl, 4-phenyl-indenyl) zirconium catalyst and diethylsilylbis(2-methyl, 4-phenyl-indenyl) zirconium catalyst; or wherein the bridged bis(indenyl) zirconocene catalyst is selected from the group consisting of: ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride and diethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl.

7. The process of claim 6, wherein the bridged bis(indenyl)zirconocene catalyst is rac-dimethylsilylene-bis(4,5,6,7-tetrahydro-1-indenyl)zirconium(IV) dichloride.

8. A membrane comprising the post-reactor blend according to any one of claims 1 to 4.

9. The film of claim 8, wherein the film is a monolayer film consisting of one layer, and wherein the one layer comprises the post-reactor blend according to any one of claims 1 to 3; or wherein the film is a multilayer film consisting of 3 to 12 layers, wherein at least one of the 3 to 12 layers comprises the post-reactor blend according to any one of claims 1 to 4.

10. The film of claim 8, wherein the film is a multilayer film consisting of 3 to 12 layers, the multilayer film comprising 2 to 4 outer layers and 1 to 8 core layers; wherein at least one outer layer independently comprises 70 wt% to 98 wt% of the C4-LLDPE and 30 wt% to 2 wt% of the C6-LLDPE, all based on the total weight of the C4-LLDPE plus the C6-LLDPE in the at least one outer layer; and wherein at least one core layer independently comprises 80 wt% to 100 wt% of the C4-LLDPE and 20 wt% to 0 wt% of the C6-LLDPE, all based on the total weight of the C4-LLDPE plus the C6-LLDPE in the at least one core layer.

11. A method for preparing the multilayer film according to claim 10, the method comprising: The multilayer film consisting of 3 to 12 layers is prepared by extruding at least one melt of the LLDPE blend and optionally a melt of the C4-LLDPE through different dies among 3 to 12 dies.

Citation Information

Patent Citations

  • Ethylene copolymers, film and polymerization process

    CN104470955A

  • Blends of linear low density polyethylenes

    CN110730802A

  • Modified spray-dried ziegler-natta (PRO)catalyst systems

    CN111315787A

  • Low comonomer incorporating metallocene catalyst compounds

    CN1545523A

  • Blends of linear low density polyethylene, polypropylene and aromatic polymers and high modulus films thereof

    EP0238756A2